2012
DOI: 10.1021/la304028f
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Substrate Wettability in Nanoparticle Transfer from Wrinkled Elastomers: Fundamentals and Application toward Hierarchical Patterning

Abstract: We report on the role of surface wettability during the printing transfer of nanoparticles from wrinkled surfaces onto flat substrates. As we demonstrate, this parameter dominates the transfer process. This effect can further be utilized to transfer colloidal particles in a structured fashion, if the substrates are patterned in wettability. The resulting colloidal arrangements are highly regular over macroscopic surface areas and display distinct pattern features in both the micrometer and nanoscale regime. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…Previous work has shown that wrinkle-assisted assembly requires strongly hydrophilic (ideally, completely wetting) substrates. 19 Thus, as-received nanorods are not appropriate, as they are only colloidally stable in the presence of an excess of CTAB. The amphiphilic character of CTAB however strongly influences the wetting behaviour of the nanoparticle solution on the substrate and results in a contact angle of 32 ± 0.8° for hydrophilised PDMS.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that wrinkle-assisted assembly requires strongly hydrophilic (ideally, completely wetting) substrates. 19 Thus, as-received nanorods are not appropriate, as they are only colloidally stable in the presence of an excess of CTAB. The amphiphilic character of CTAB however strongly influences the wetting behaviour of the nanoparticle solution on the substrate and results in a contact angle of 32 ± 0.8° for hydrophilised PDMS.…”
Section: Resultsmentioning
confidence: 99%
“…41 Template-assisted organization imposes several requirements on the colloidal interactions of the employed particles; long-range electrostatic attraction between the template and the particles has to be avoided and at the same time, the particles should maintain colloidal stability at elevated concentrations and possess hydrophilic surfaces. 42 As prepared, the particles are coated by a layer of cetyltrimethylammonium bromide (CTAB), of which a large excess present in solution is necessary in order to ensure colloidal stability. During template-assisted assembly, this surfactant strongly adsorbs onto the surface of the used silica substrate, changing the wettability in an unfavorable fashion.…”
Section: Colloidal Building Blocksmentioning
confidence: 99%
“…Furthermore, Hanske and co‐workers used a combined approach of chemical patterning and template assisted in combination with microcontact printing to organize nanoparticles in complex structures achieving a selective adsorption of particle lines in concrete regions of the substrate. This technique leads not only to linear assemblies, but also to grid like structures 186…”
Section: Surface Microstructures From Particles Assembled On Biomimentioning
confidence: 99%